The role of sports management to increase environmental awareness in the Youth and Sports Forum (Damu Journal of Sport Sciences, 2024)
Given the importance of the topic of sports management and what it includes in terms of planning, organizing, directing, implementing and monitoring sports activities and events in various sports institutions from sports clubs, federations and youth and sports forums in general. From this, the research aims to identify the role of sports management in developing some sports activities and serving the environment, as well as identifying the role of sports management in favoring some sports activities, serving the environment and increasing environmental awareness, as well as identifying the most important difficulties facing youth and sports forums in favoring some environmental activities.The researcher used the descriptive browser to suit the nature of the research. The research community was determined from the members of the youth and sports forums affiliated to the Directorate of Youth and Sports of Babylon, numbering (340) people (males and females), then they were selected randomly. The sample represents (19%) of the total study community, which is (1807) individuals from the research sample. The research came out with a set of conclusions: First, there is a difference between planning and application in the field of environmental service, as planning efficiency was better than application. Second, the important role played by some sports activities related to youth forums was not effective in the appropriate manner in serving the environment. In addition to the weak role of the media and material capabilities, which are considered among the most important obstacles facing some sports activities, especially youth forums, whether sports or environmental, as well as the fact that the sports administration in youth and sports forums does not focus much on the environment in its work, but rather on sports, cultural and artistic activities.